2001
DOI: 10.1046/j.1365-2842.2001.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and wettability of enamel and dentine surfaces prepared with different dental burs

Abstract: The aim of dental adhesive restorations is to produce a long lasting union between the restoration and the tooth structure. This bond depends on many variables including the geometry of the preparation and the type of bonding agent or luting cement. It is therefore suggested that the topography of the tooth surface may influence the wettability and the bonding quality of adhesive systems. This study measured the surface roughness and wettability of enamel and dentine after preparation with different dental bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 16 publications
2
63
1
2
Order By: Relevance
“…The diamond bur created a thicker smear layer than did other treatments, and formed a rough dentin surface with deeper and uniform grooves, different from those created by the carbide bur 1,4 ( Figures 1A1 and 2B). Evaluating dentin permeability before and after application of Clearfil SE Bond, Vaysman et al 18 (2003) observed that the highest reduction in bonded dentin permeability and an increase in sealing ability occurred when the self-etching adhesive system was applied to the roughest dentin surface.…”
Section: Discussionmentioning
confidence: 91%
“…The diamond bur created a thicker smear layer than did other treatments, and formed a rough dentin surface with deeper and uniform grooves, different from those created by the carbide bur 1,4 ( Figures 1A1 and 2B). Evaluating dentin permeability before and after application of Clearfil SE Bond, Vaysman et al 18 (2003) observed that the highest reduction in bonded dentin permeability and an increase in sealing ability occurred when the self-etching adhesive system was applied to the roughest dentin surface.…”
Section: Discussionmentioning
confidence: 91%
“…The wetting of the adherent surface by an adhesive could be indicated by the contact angle. Measurements of the contact angle on adherent surfaces provide information about the surface free energies that relate to the bonding characteristics of solids [11][12][13] . The surface free energy of a solid (γS) is defined as the sum of the dispersion, hydrogen bonding, and polar forces.…”
Section: Discussionmentioning
confidence: 99%
“…21 Surface roughness plays as the prime criterion in enhancing adhesion of restoration by increasing the surface area and improving the wettability properties. 3 It is measured in Ra (arithmetic mean) and Rv (depth of surface roughness) values. 3 Though scanning electron microscope (SEM), transmission electron microscope (TEM), mechanical profilometer, light microscope, and atomic force microscope have been used for measuring surface roughness values, the inability of the sensor needles of these devices to penetrate all the irregularities have brought a 3D profilometer into focus.…”
Section: Discussionmentioning
confidence: 99%
“…3 It is measured in Ra (arithmetic mean) and Rv (depth of surface roughness) values. 3 Though scanning electron microscope (SEM), transmission electron microscope (TEM), mechanical profilometer, light microscope, and atomic force microscope have been used for measuring surface roughness values, the inability of the sensor needles of these devices to penetrate all the irregularities have brought a 3D profilometer into focus. This has the distinct advantage of being noncontact, nondestructive, and quick quantitative measurement for surface roughness providing multiples descriptions of surface roughness profiles beyond the ability of 2D surface profilometer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation